Scope for utilization of sunflower heads as animal feed in Karnataka state - ANANDAN, S; ANIL KUMAR, G K; RUDRASWAMY, M S; RAMANA, J V; RAMACHANDRA, K S (The Indian Journal of Animal Sciences, 2014)
A survey was carried out to assess the utilization pattern of sunflower hl!ads (SFH) in the districts ofBellary, Raichur and Chitradurga, which are the major sunflower growing areas of the Karpataka state. The survey revealed that currently sunflower heads are not being fed to any class of livestock, and are mainly used for composting or burnt or dumped on way side. Even though sunflower heads are not being fed, the survey revealed that animals consumed SFH in a limited way. Small ruminants have a greater liking for SFH than the large ruminants. The major reason ascribed for not feeding SFH is lack of tradition and availability of other feeds in sufficient quantities. The chemical composition and in vitro studies revealed that SFH is nutritionally better than many of the commonly used roughages. Proper extension and demonstration of utilization of SFH is requited for popularizing the use of SFH as livestock feed.